FASILITAS PENGOLAHAN SAMPAH DENGAN PENERAPAN TEKNOLOGI INSENERASI DI MAMMINASATA - Suradin, Muhammad Zaldi; Burhanuddin, Burhanuddin (Nature: National Academic Journal of Architecture, 2015)
Waste in Indonesia is a common problem as part of the dynamics of human life. Based on data from the Medium Term Development Plan (RPJMD) South Sulawesi province Years 2013-2018, the total volume of waste generated and the production of Makassar, Maros, Gowa, and Takalar estimated rate of waste generation as much as 9076.949 m3 / person / day. Reports purpose of this design is to provide a waste processing facility to accommodate the main sewage treatment process and supporting activities such as: a place of education and research on garbage, as well as administrative management activity waste treatment facilities. The result of this report will be at the Tata-inspired landscape from the analysis of satellite imagery line pattern observation planning area which is then used as the pattern of the building site. Consideration of building orientation analysis is carried out wind and solar path through autodesk software project Vasari. Tread is designed with a separate circulation system between the interests of waste treatment facilities with a visit by a community activity to minimize croos so as to provide comfort to the users of the building. The mass of the building is designed with a series of integral system, starting from the main building is placed in the north, and then connected by a visitor center area that extends down the waste processing area to the southern area of residues in the region.